TINJAUAN YURIDIS HUBUNGAN PENERAPAN CHOICE OF LAW DENGAN KEWENANGAN MENGADILI OLEH PENGADILAN (ANALISIS PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 1935 K/PDT/2012) - CHARLENE FORTUNA TANIA (PREMISE LAW JURNAL, 2017)
Almost all business activities are initiated by a contract. It can be either a national or an international contract. An international contract is a contract which contains foreign elements. The characteristic of an international contract is the main element i.e. freedom element for all parties to take choice of law. Choice of law in the national law of a country does not mean that the judiciary of that country is automatically authorized to settle any dispute. It means that choice of law is not like choice of forum. This thesis discusses the problem of choice of law, choice of forum and the authority of Indonesian judiciary to hear the dispute of an international business contract; and analyzes the law implementation of the Panel of Judges related to the authority to hear the international business contract in the ruling of the Supreme Court No. 1935 K/Pdt/2012.Keywords: Choice of Law, Choice of Forum, Authority to Hear.